2022
DOI: 10.1186/s12877-022-03460-2
|View full text |Cite
|
Sign up to set email alerts
|

Interventions addressing functional abilities of older people in rural and remote areas: a scoping review of available evidence based on WHO functional ability domains

Abstract: Background The World Health Organization (WHO) encourages healthy ageing strategies to help develop and maintain older people’s functional abilities in five domains: their ability to meet basic needs; learn, grow, and make decisions; be mobile; build and maintain relationships, and contribute to society. This scoping review reports the available evidence-based interventions that have been undertaken with people ≥ 50 years of age in rural and remote areas and the outcomes of those interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Indeed, a review aiming at identifying evidence gaps in health, social care and technological interventions to improve the functional ability of older persons showed that the most commonly used intervention was home-based rehabilitation [ 20 ]. Another review found that education, skills training, exercise, and physical activity—traditional rehabilitation interventions—were the most commonly provided interventions to improve the functional ability of older persons in rural and remote areas [ 21 ]. Recognising the potential of rehabilitation, the WHA adopted in May of 2023 a resolution for “ Strengthening rehabilitation in health systems”, stating that the provision of expanding rehabilitation to all levels of health, from primary to tertiary is essential to ensure the availability and affordability of quality and timely rehabilitation services for all [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a review aiming at identifying evidence gaps in health, social care and technological interventions to improve the functional ability of older persons showed that the most commonly used intervention was home-based rehabilitation [ 20 ]. Another review found that education, skills training, exercise, and physical activity—traditional rehabilitation interventions—were the most commonly provided interventions to improve the functional ability of older persons in rural and remote areas [ 21 ]. Recognising the potential of rehabilitation, the WHA adopted in May of 2023 a resolution for “ Strengthening rehabilitation in health systems”, stating that the provision of expanding rehabilitation to all levels of health, from primary to tertiary is essential to ensure the availability and affordability of quality and timely rehabilitation services for all [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be attributed to differences in baseline functional status, lifestyle factors, or other socioeconomic determinants between the two populations. Previous research has suggested that rural older adults may face unique challenges in terms of access to healthcare and supportive resources, which could impact their functional abilities (19). The intervention may have addressed some of these challenges, leading to improved ADL performance in the rural group.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic covariates included age at baseline (continuous variable), sex (male, female), education level (less than secondary school, secondary school or higher), and marital status (married, unmarried). Health behavior and clinical risk covariates included smoking, drinking, and healthy aging score (HAS) (low, high levels), following previous study methodology 3–5,32 . Further details for each variable are available on the CHARLS Website (http://charls.pku.edu.cn/).…”
Section: Methodsmentioning
confidence: 99%